2015
DOI: 10.1111/jfbc.12165
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Treated Solar Sea Salt Has Antioxidant Activity In Vitro and Produces Less Oxidative Stress in Rats Compared with Untreated Solar Sea Salt

Abstract: We have investigated the in vitro and in vivo antioxidative activity of solar sea salts(SS) roasted with (BS) or without (RS) bamboo, which are widely consumed as dietary salts in Korea. BS exhibited antioxidative activity in the in vitro assays of various radical-scavenging activities and DNA oxidation. RS also scavenged superoxide radicals and inhibited DNA oxidation. However, SS did not exhibit antioxidative activity in vitro. Sprague-Dawley rats were orally administered various salts (1.8 g NaCl equivalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Interestingly, however, recent clinical studies have indicated that salts enriched with the minerals magnesium, potassium, and calcium could reduce the risk of high blood pressure and osteoporosis (Tucker and others ; Larsson and others ). Although the relationship between salt intake and health is still controversial, there is increasing interest in the potential health benefits of some specialty salts, such as mineral‐rich sea salt (MRS) and bamboo salt (Zhao and others ; Gao and others ). In particular, recent studies on the quality of fermented foods, such as kimchi (Chang and others ) and doenjang (Chang and others ), have also revealed that characteristics such as texture and taste were significantly affected by the salt contents and types.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, however, recent clinical studies have indicated that salts enriched with the minerals magnesium, potassium, and calcium could reduce the risk of high blood pressure and osteoporosis (Tucker and others ; Larsson and others ). Although the relationship between salt intake and health is still controversial, there is increasing interest in the potential health benefits of some specialty salts, such as mineral‐rich sea salt (MRS) and bamboo salt (Zhao and others ; Gao and others ). In particular, recent studies on the quality of fermented foods, such as kimchi (Chang and others ) and doenjang (Chang and others ), have also revealed that characteristics such as texture and taste were significantly affected by the salt contents and types.…”
Section: Introductionmentioning
confidence: 99%
“…Solar sea salt and bamboo salt might play a role in attenuating oxidative stress and inflammation induced by dietary salt containing only NaCl [31,32]. K, Mg, and Ca are the main minerals in solar sea salt and bamboo salt.…”
Section: Discussionmentioning
confidence: 99%